Optimalisasi Manajemen Jurnal Ilmiah melalui Pelatihan Terpadu di Universitas Pat Petulai - Parwito, Parwito; Indrayanto, Indrayanto; Susanto, Edy; Sinta, Dwi; Murlena, Murlena; Wijaya, Nopa; Ulhaqiyah, Asyifa (Jurnal PADAMU NEGERI (Pengabdian pada Masyarakat Bidang Eksakta), 2024)
The integrated training in scientific journal management at Pat Petulai University was designed to enhance the understanding and skills of journal managers regarding the use of Open Journal Systems (OJS), the peer review process, and journal accreditation standards. Evaluation results indicate that participants found the training highly beneficial and relevant to their needs. Participants demonstrated high enthusiasm during the training, reflected in their active participation in discussions and practical sessions. Despite weaknesses such as limited time for practice sessions, recommendations for improvements have been made to enhance future training effectiveness. Overall, the results show that the training successfully achieved its goals and positively contributed to the quality and efficiency of journal management at the university.